Analisis Semiotika Representasi Pria Metroseksual dalam Video Musik Seventeen “Thanks” - Grace Harpono; H.H Daniel Tamburian (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Metrosexual men are men who take care of themselves and care about their appearance, at this time this is a natural thing and there are many beauty products specifically for men to maintain their appearance. At this time, the writer examines this through music videos, with the aim of seeing how the metrosexual male representations that occur in the Seventeen music video entitled 'Thank you'. To be able to do this analysis, the writer conducted research by analyzing the clips in the music video, therefore in this study the writer chose to use qualitative research methods. This research technique uses Roland Barthes' semiotic analysis theory which sees signs as denotations and connotations. With data techniques using observation techniques. The observation technique referred to by the author is to make observations made by the author of the Seventeen music video entitled